Interferometria de onda térmica com radiação da lâmpada de arco xenônio : teste em cimento endodôntico rápido - Picolloto, Angela Maria (2012)
This experimental technique Thermal Wave Interferometry (TWI) with white light instead laser heating is applied in the study and analysis of thermophysics parameters of Fast Endodontic Cement. This new dental cement is based on clínquer added barium sulphate and emulsion gel and was desenvolved in the Physics-Chemical Department of UNESP-Brazil. Prior samples present composition dependent upon grain sizes (sieveds for 25, 38, 45 and 53 μm) and stabilized in gel emulsion with (140, 150, 160 and 170 μL). All experiments owing thermophysics parameters were carried out by TWI with arc Xe lamp. The opaque model was modified accordingly to take into account sample adherence on substrate, as needed by this technique. Results besides toward Mineral Trioxide Aggregate (MTA) properties, agreeing pretty well with its thermophysics properties. The used of arc Xe lamp was a prior validated with measurements of thermal grease, Portland cement and epoxy resin. All results were in agreement with literature.